Система оплаты труда и государственное обеспечение оплаты труда работника - Ефремова, А.А.; Ревега, К.В. (Культура народов Причерноморья, 2013)
Статья посвящена рассмотрению выбора систем оплаты труда, а также проблеме
государственного обеспечения оплаты труда работника. В статье рассмотрены сущность заработной
платы, выбор систем и форм оплаты труда, исследованы государственные методы регулирования
оплаты труда, установление размера минимальной заработной платы.
Ключевые слова: заработная плата, системы оплаты труда, формы оплаты труда, минимальная
заработная плата. Стаття присвячена розгляду вибору систем оплати праці, а також проблемі державного
забезпечення оплати праці працівника. У статті розглянуто сутність заробітної плати, вибір систем і
форм оплати праці, досліджені державні методи регулювання оплати праці, встановлення розміру
мінімальної заробітної плати.
Ключові слова: заробітна плата, системи оплати праці, форми оплати праці, мінімальна заробітна
плата. The article considers the choice of pay systems, as well as the problem of state security for the
payment of the employee. The article describes the nature of wages, selection systems and forms of payment,
examined state regulation methods of remuneration, setting the amount of the minimum wage. State sets
minimum wages on the basis of the subsistence minimum, thus trying to provide decent wages to the employee's
labor. Over the past year, Ukraine has seen the growth of a living wage and the minimum wage, which could
lead to the stabilization of the level of employment in the state.
Keywords: wages, salary system, form of payment, the minimum wage.